2013
DOI: 10.1111/imig.12108
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Change in Religious Salience Among Immigrant Families in Four European Countries

Abstract: This paper investigates religiosity among immigrant children in four European countries: England, Germany, the Netherlands and Sweden. Drawing on major strands of theories in the sociology of religion and of migration, we analyse intergenerational change in religiosity within immigrant families of different religious affiliation and test how far common arguments can contribute to explaining existing patterns. We overcome several challenges and shortcomings in this field by studying adolescent-parent dyads. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 41 publications
7
43
0
4
Order By: Relevance
“…Research has shown that the psychological impact of unemployment is smaller, and adaptation faster, among religious people (Lechner and Leopold 2015). In contrast to the factors already discussed, compositional differences in terms of religiousness benefit immigrants, as they attend religious services more frequently than German natives (Jacob and Kalter 2013).…”
Section: Religiousnessmentioning
confidence: 93%
“…Research has shown that the psychological impact of unemployment is smaller, and adaptation faster, among religious people (Lechner and Leopold 2015). In contrast to the factors already discussed, compositional differences in terms of religiousness benefit immigrants, as they attend religious services more frequently than German natives (Jacob and Kalter 2013).…”
Section: Religiousnessmentioning
confidence: 93%
“…According to assimilation theory, structural and cultural integration are mutually reinforcing (Jacob and Kalter 2013). In other words, we would expect that support of the Scandinavian gender egalitarian values, including mothers' employment, would be more likely the more immigrants participate in overall society, the more fluent they become in the language of the host country and the more economically integrated they become.…”
Section: Migration and Cultural Adaptationmentioning
confidence: 99%
“…General assimilation theory predicts that immigrants, over time and in particular over generations, will become more similar to members of the host societies. Implicitly assumed is that exposure to the host society's institutions and contact with the native population will gradually result in both economic and cultural integration (Alba and Nee 1997;Alba 2005;Jacob and Kalter 2013). While most empirical studies have concentrated on economic integration, there is now also a growing body of literature on cultural and attitudinal adaptation (Algan et al 2012;Maliepaard, Lubbers, and Gijsberts 2010).…”
Section: Migration and Cultural Adaptationmentioning
confidence: 99%
“…Andere Studien kommen dagegen zu dem Ergebnis einer größeren inter-generationalen Stabilität von Religiosität unter Muslimen (für Deutschland vgl. Diehl und Koenig 2009;Jacob und Kalter 2013). Wieder andere Studien betonen die Kontextabhängigkeit religiöser Dynamiken und verweisen dazu auf direkte Effekte xenophober Einstellungen in der lokalen Umwelt auf muslimische Religiosität (Connor 2010) oder auf vermittelnde Effekte des Ausmaßes institutioneller Anerkennung des Islam auf den Zusammenhang von muslimischer Religiosität und sozialer oder struktureller Integration (Fleischmann und Phalet 2012).…”
Section: Einleitung: Religiosität Türkischer Und Polnischer Neuzuwandunclassified